An analysis of study-abroad students: how the 'self' articulates experiences and encounters in different cultural settings - Chingore, Tatenda Millicent Nichole (Department of Sociology, 2016)
Twenty-first century globalisation has brought with it, distinction among students through the Internationalisation of Higher Education (IHE). The effects of globalization and the IHE has been categorised as "preparing students for the globalizing world, suggesting new pedagogies and institutional settings that nurture 'global consciousness'" (Mansilla & Gardner, 2007: 56.) With the increase in mobility and hyper-connectivity, an education has become more than what is taught within the confines of a classroom or university. Studying abroad has become a significant component within the academic arena that allows students the privilege and opportunity to develop intercultural competence through first-hand experience This study seeks to explore the articulation of experiences and encounters from the perspective of the study abroad student exposed to cultural settings different from their own. This dissertation will place particular emphasis on the articulation of the responses and approaches taken by individuals of their respective encounters and experiences, using the Circuit of Culture as a link drawing together the themes (Re)Construction of Self Identity; 'Fitting In' and Adaptation; Developing Intercultural Competence and Society as we now know it, to give a holistic, interpretive understanding into the meanings and outcomes produced by the relationship between the constructions and perceived ideologies of both the study abroad student and the hosts collective. The study is amalgamation of responses from personal narrations given by eight participants, as well as a discussion with four individuals in a focus group from different countries. They reveal the importance of the self, from both the personal and social viewpoint to be able to comprehend the actions and reactions taken to construct, adapt, assimilate and learn from the experience. Discoveries uncover difference as a component that exists between the self and the other in a number of ways through how they classify and identify each other. As a result, slight but significant changes in perceptions can be noted.